Linking core self-evaluation, career exploration, person-environment fit, and career indecision in school-to-work transition: a conceptual framework - Kou, Qi; Mohd Rasdi, Roziah; Hilary Osolase, Ehikioya; Md Rami, Ahmad Aizuddin; Muhama Nasharudin, Nurfazreen Aina (Human Resource Management Academic Research Society, 2024)
Based on the social cognitive career self-management model, the conceptual framework developed for this study aimed at contributing to the important, yet challenging phase of school-to-work transition for young adults who often encounter problems related to indecision and being unable to take affirmative actions required for career development. Predicated on empirical evidence, this study considered that the sub-traits of core self evaluation (i.e., self-esteem, generalized self-efficacy, emotional stability, and locus of control) are predictors of career indecision. Additionally, career exploration was adopted as the mediator for explaining the mechanism between the independent and dependent variables, as person-environment fit has the potential to be a moderator for describing the inconsistency in the effects of career exploration on career indecision. This study was concluded with a focus on how the practical implications have the potency to facilitate successful school-to-work transition among young undergraduate students, in addition to seeing the positive impact which human resource development (HRD) provides towards effecting a successful transition.